2021
DOI: 10.1109/tim.2021.3111995
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Harmonics With Inductive Voltage Transformers in Presence of Subharmonics

Abstract: The measurement of harmonics is one of the key tasks in the modern power systems, performed basically for power quality assessment, verification of planning levels compliance, immunity and compatibility purposes and so on. Especially at Medium Voltage (MV) and High Voltage (HV) levels, harmonics are always measured through Voltage and Current Transformers (VTs and CTs), which very often are inductive. Recent papers show that inductive VTs and CTs, due to the intrinsic iron core nonlinearity, can introduce erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…At present, there are few papers in the literature dealing with metrological performances of ITs used for PQ measurement. Some authors of this paper have already shown that the metrological performances of ITs in the presence of PQ phenomena can drastically change [ 30 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Analysis Of the Literature And Standards Regarding Its And P...mentioning
confidence: 99%
“…At present, there are few papers in the literature dealing with metrological performances of ITs used for PQ measurement. Some authors of this paper have already shown that the metrological performances of ITs in the presence of PQ phenomena can drastically change [ 30 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Analysis Of the Literature And Standards Regarding Its And P...mentioning
confidence: 99%
“…There is a normative gap regarding IT performance verification in both supply systems when ITs are used in PQ measurements. Information and data on this issue are partially provided from both the literature [ 14 , 15 , 16 , 17 , 18 , 19 ] and the technical report [ 20 ]. Moreover, in this respect, a European metrology research project, EMPIR 19NRM05 IT4PQ [ 21 ], has been funded.…”
Section: Introductionmentioning
confidence: 99%
“…DC voltage and more in general, low-frequency disturbances can badly influence the behavior of voltage transformers (VTs) [ 15 ]. When a transformer is supplied with a DC waveform, a DC magnetization bias of the magnetic circuit will result.…”
Section: Introductionmentioning
confidence: 99%
“…Subharmonics are particular cases of interharmonics; in fact, they are defined as components with frequencies lower and, consequently, not integer multiples of the fundamental frequency at which the supply system is designed to operate. Subharmonics are injected into the power grid by distributed generation systems, like wind farms [15], [16], hydro-powers [17] or photovoltaic plants [18], and loads, like arc furnaces and cyclo-converters [19]- [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the resolution of 5 Hz might not be sufficient for proper detection of subharmonics, especially when subharmonics with frequency not integer multiple of 5 Hz are present, since they produce spectral leakage that can badly affect the results [24]. The authors in [21] have experimentally shown how subharmonics, having realistic amplitudes and frequencies, can impact on the performance of inductive Voltage Transformers (VTs) when they are used for harmonic measurements.…”
Section: Introductionmentioning
confidence: 99%